MITF is a critical regulator of the carcinoembryonic antigen‐related cell adhesion molecule 1 (CEACAM1) in malignant melanoma. (November 2015) - Ullrich, Nico; Löffek, Stefanie; Horn, Susanne; Ennen, Marie; Sánchez‐del‐Campo, Luis; Zhao, Fang; Breitenbuecher, Frank; Davidson, Irwin; Singer, Bernhard B.; Schadendorf, Dirk; Goding, Colin R.; Helfrich, Iris
Summary The multifunctional Ig‐like carcinoembryonic antigen‐related cell adhesion molecule 1 (CEACAM1) is neo‐expressed in the majority of malignant melanoma lesions. CEACAM1 acts as a driver of tumor cell invasion, and its expression correlates with poor patient prognosis. Despite its importance in melanoma progression, how CEACAM1 expression is regulated is largely unknown. Here, we show that CEACAM1 expression in melanoma cell lines and melanoma tissue strongly correlates with that of the microphthalmia‐associated transcription factor (MITF), a key regulator of melanoma proliferation and invasiveness. MITF is revealed as a direct and positive regulator for CEACAM1 expression via binding to an M‐box motif located in the CEACAM1 promoter. Taken together, our study provides novel insights into the regulation of CEACAM1 expression and suggests an MITF‐CEACAM1 axis as a potential determinant of melanoma progression.